Implementation Model of Character Education Values in the Islamic Boarding School System - Lasmiadi; Maya Febriani Chandra; Alhairi (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
School is a time of character growth, which greatly determines a person's moral and intellectual foundations throughout his life. To build students' personalities, education must have a mission that shapes students' personalities. Character education basically focuses on building students who are cultured and dignified. All characters can change, and education is needed to change character. Using qualitative research methods with a phenomenological approach. Basically, the results of the research show that both Islamic boarding schools both implement the character education values ​​proclaimed by the Ministry of National Education, namely values ​​originating from religion, which in this case is Islam, Pancasila, culture, which are in accordance with the objectives of national education, namely: ( 1). Religious, (2). Honestly, (3). Tolerance, (4). Discipline, (5). Hard work, (6). Creative, (7). Independent, (8). Democratic, (9). Curiosity, (10). National spirit, (11). Love of the homeland, (12). Appreciating achievements, (13). Friendly/communicative, (14). Love peace, (15). Likes to read, (16). Care for the environment, (17). Social care, and (18). Responsibility. Supporting factors in implementing the character education model are: The presence of parental participation, Motivation, Leadership, and commitment to cooperation between the Islamic boarding school and parents, while the inhibiting factors in implementing the character education model are: Still minimal attention from parents, Insufficient environment. support, and limited supervision from teachers, caregivers and parents.